Supercapacitors: An Emerging Energy Storage System - Muhammad Faisal Iqbal; Farooq Nasir; Fiza Shabbir; Zaheer Ud Din Babar; Muhammad Farooq Saleem; Kaleem Ullah; Nana Sun; Faizan Ali (Advanced Energy & Sustainability Research)
Electrochemical capacitors are known for their fast charging and superior energy storage capabilities and have emerged as a key energy storage solution for efficient and sustainable power management. This article comprehensively explores the fundamental principles, architectural advancements, and material innovations underpinning supercapacitor technology. It covers the evolution of supercapacitor performance, the comparison of pseudocapacitors, double‐layer capacitors, electrolytes, and the integration of innovative nanostructured materials, such as carbon nanotubes, transition metal oxides, MXene, and graphene, and it investigates the hybrid systems that bridge the gap between capacitors and batteries. The article also discusses the future perspectives of supercapacitor technology. By examining emerging trends and recent research, this review provides a comprehensive overview of electrochemical capacitors as an emerging energy storage system.